Stakeholders' perspectives on parental engagement in Tanzanian pre-primary schools: Exploring opportunities and challenges - Johnson Wilson Kojo; Abdallah Jacob Seni; Placidius Ndibalema (Academy of Cognitive and Natural Sciences, 2024)
The purpose of this study was to explore the stakeholders' perspectives on parental engagement in pre-primary schools in Nzega District, Tanzania. This study, therefore, explored how stakeholders define parental engagement and identify behaviours that are indicative of it. The study was qualitative, and a phenomenological design was adopted. It consisted of six focus group sessions with a total of 34 parents. A semi-structured interview was conducted with five pre-primary school teachers, four head teachers and five chairpersons of the school committees in the six selected schools. It deployed Braun and Clarke \cite{braun2006using} six steps of qualitative data analysis. Results showed that there was a slight variation within and between stakeholder groups on how they define and experience parental engagement. To enhance common understanding, participants felt the need to enhance parents' competencies to support their children's learning at home and in school. This study, therefore, recommends the need for intervention programmes that will empower parents to effectively engage in their children's learning opportunities at home and in pre-primary schools.